2018
DOI: 10.1111/ggr.12202
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Nanosecond Laser Ablation Multi‐Collector Inductively Coupled Plasma‐Mass Spectrometry for Pb and Sr Isotopic Determination in Archaeological Glass: Mass Bias Correction Strategies and Results for Corning Glass Reference Materials

Abstract: This work presents an evaluation of various methods for in situ high‐precision Sr and Pb isotopic determination in archaeological glass (containing 100–500 μg g−1 target element) by nanosecond laser ablation multi‐collector‐inductively coupled plasma‐mass spectrometry (ns‐LA‐MC‐ICP‐MS). A set of four soda‐lime silicate glasses, Corning A–D, mimicking the composition of archaeological glass and produced by the Corning Museum of Glass (Corning, New York, USA), were investigated as candidates for matrix‐matched r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 53 publications
0
24
0
Order By: Relevance
“…The plasma was operated under wet conditions by pumping 100 μl/min 3% HNO 3 solution to improve stability. Corning D was used as a secondary standard for this analysis; its isotopic composition and suitability as standard are discussed elsewhere (Van Ham-Meert et al 2018). Instrumental settings are found in Table 3.…”
Section: Pneumatic Nebulisation-multicollector-inductively Coupled Plasma-mass Spectrometrymentioning
confidence: 99%
“…The plasma was operated under wet conditions by pumping 100 μl/min 3% HNO 3 solution to improve stability. Corning D was used as a secondary standard for this analysis; its isotopic composition and suitability as standard are discussed elsewhere (Van Ham-Meert et al 2018). Instrumental settings are found in Table 3.…”
Section: Pneumatic Nebulisation-multicollector-inductively Coupled Plasma-mass Spectrometrymentioning
confidence: 99%
“…Some authors have reported that the isotope ratio drift encountered in the case of short transient signals can be corrected for by taking into account the differences in response times between Faraday cups or between a Faraday cup and an ion counter or by correcting the values for the slow response of the Faraday preamplifier . Therefore, strategies to correct for instrumental mass discrimination in LA–MC-ICP-MS and the effects of relevant interferences need to be evaluated . Although nanosecond-based LA systems are more susceptible to matrix effects and isotope fractionation than femtosecond-lasers, improvements in the instrumentation and correction strategies developed in recent years were able to mitigate these effects and to generate accurate and sufficiently precise isotope ratio results in some contexts. , Moreover, nanosecond-based LA systems are easier to operate and are more affordable, as a result of which they are considerably more widespread.…”
mentioning
confidence: 99%
“…19 Therefore, strategies to correct for instrumental mass discrimination in LA−MC-ICP-MS and the effects of relevant interferences need to be evaluated. 20 Although nanosecond-based LA systems are more susceptible to matrix effects and isotope fractionation than femtosecond-lasers, 21 improvements in the instrumentation and correction strategies developed in recent years were able to mitigate these effects and to generate accurate and sufficiently precise isotope ratio results in some contexts. 20,22 Moreover, nanosecond-based LA systems are easier to operate and are more affordable, as a result of which they are considerably more widespread.…”
mentioning
confidence: 99%
“…Another technique worth mentioning is laser ablation (LA) ICP-MS. Van Ham-Meert and co-authors 124 published an article about LA-ICP-MS for Pb and Sr isotopic determination in archaeological glass. This technique was also used for provenancing of ceramics, 98,99 as well as for cultural heritage research.…”
Section: Other Techniquesmentioning
confidence: 99%